Mental health and well-being in adolescent and young adult refugees in Sweden: A cross-sectional study of accompanied and unaccompanied individuals - Erica Mattelin; Amal R. Khanolkar; Johan Andersson; Hania Kutabi; Laura Korhonen (Comprehensive Psychiatry)
Background: Currently, approximately 100 million people are displaced worldwide, including children and young adults. Previous studies showed exposure to violence and posttraumatic stress disorder (PTSD) are common in this sub-population. However, we still lack comprehensive data on well-being, mental health, and the ability to function. Methods: This study included 291 adolescent (aged 12–17 years) and young adult (18–25 years) refugees recruited nationwide in Sweden between 2019 and 2022. Sociodemographic, mental health and well-being-related data (well-being, post-traumatic stress symptoms, psychiatric diagnoses, and functional ability) were collected using semi-structured interviews with structured components. Associations between accompanied status and well-being/depression/suicidal thoughts, generalized anxiety disorder/panic disorder/PTSD symptoms, and functional ability were analyzed using linear and logistic regression, adjusted for age, gender, parental education, asylum status, and region of origin. Findings: Most study participants (mean age 17·9 years) originated from the Middle East and North Africa (70·6 %) or Sub-Saharan Africa (27·0 %). 16·1 % of adolescents and 32·3 % of young adults were unaccompanied. Nearly the entire study sample had experienced violence (92·8 %). However, the sample had a low prevalence of psychiatric diagnoses. For example, only 5·9 % fulfilled the criteria for clinical depression. Self-reported well-being (WHO-5, 71·09 (23·91)) and observer-rated functional ability (GAS/GAF, 81·76 (14·15)) were high. There were no significant differences in diagnosis prevalence by gender. However, significant differences existed between accompanied versus unaccompanied groups. Being an unaccompanied refugee individual was associated with a higher risk of suicidal thoughts, adjusted odds ratio, aOR 5·66 (95 % CI 2·15–14·88), higher rates of post-traumatic stress disorder symptoms β = 0·72 (0·39–1·05), lower mental well-being β = −10·86 95 % CI (−18·23— -3·48) and lower functional ability β = −9·38 (−13·84— -4·92). There were no differences in outcomes by gender except for worse well-being in males (β = 6·83 (1·01–12·66)). Interpretation: In this sample, we found lower prevalence rates for all psychiatric diagnoses compared to earlier published studies. Being an unaccompanied refugee individual was a risk factor for all adverse outcomes. Future studies need to confirm the relatively low rates of psychiatric diagnoses. Regardless, the results highlight the heterogeneous needs among newly arrived refugees.